Factors associated with neonatal jaundice in a regional high-altitude hospital: a cross-sectional study - Cordova-Cairampoma, Luis (2024)
Neonatal  jaundice  is  a  condition  characterized  by  elevated  bilirubin  levels  in  newborns,  which,  if  left  untreated, can lead to serious neurological complications. This study aimed to identify factors associated with neonatal jaundice in newborns at a regional referral hospital located at a high altitude (4338 meters above  sea  level)  in  Peru.  A  cross-sectional  observational  study  was  conducted,  reviewing  the  medical  records of 206 newborns treated during the last half of 2022. Factors associated with neonatal jaundice were evaluated using logistic regression, and odds ratios (OR) were calculated as measures of association. Significant  associations  were  found  between  neonatal  jaundice  and  male  gender  (OR  =  2.01;  95  %  CI  =  1.05-3.83;  p  =  0.034),  preterm  gestational  age  (OR  =  2.91;  95  %  CI  =  1.41-6.00;  p  =  0.003),  dystocic  delivery (OR = 3.81; 95 % CI = 1.95-7.42; p = 0.001), A+ blood group and Rh factor (OR = 2.90; 95 % CI  =  1.16-4.22;  p  =  0.019),  and  low  birth  weight  (OR  =  2.38;  95  %  CI  =  1.19-4.74;  p  =  0.012).  Future  studies should include larger cohorts and further explore the impact of high-altitude geography on the development of neonatal jaundice.